2020
DOI: 10.1038/s41598-020-64276-x
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of peripheral artery disease diagnosis using exercise transcutaneous oxygen pressure measurement and post-exercise ankle-brachial index

Abstract: weak with only a fair rating with a k value of 0.23[0.04-0.41] (Table 2). The characteristics of the concordant and discordant patients are presented in Table 3. Figure 2 depicts the results of both tests in the included population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…There was no marked difference between the pre- and postoperative rest ABI. If the exercise ABI had been measured, it might have explained the reason behind the occurrence of lower-limb claudication [ 25 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no marked difference between the pre- and postoperative rest ABI. If the exercise ABI had been measured, it might have explained the reason behind the occurrence of lower-limb claudication [ 25 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…AUCs for post-exercise ABI decrease ≥18.5% and DROP ≤-15 mmHg were 0.67[0.53-0.78] and 0.67[0.53-0.78] respectively (7). We and others have previously demonstrated that discrepancies for the diagnosis of LEPAD exist between exercise criteria (Ankle pressure, post-exercise ABI and exercise-TcPO2) (8)(9)(10). Indeed, using a criterion patient can be considered as a LEPAD patient whereas using another criterion the same patient can be considered as a patient without LEPAD.…”
Section: Introductionmentioning
confidence: 95%
“…These hypotheses are of particular interest, since on the one hand, it is generally admitted that research into the consequences of ischemia in patients with claudication and an abnormal ankle to brachial index (ABI) should give further consideration to the calf muscles [8][9][10][11]; and on the other hand, it is well known that a normal ABI does not exclude the vascular origin of calf claudication, but although post exercise ABI is of interest, it cannot be used interchangeably with Ex-TcpO2 for the diagnosis of LEAD in patients with exertional symptoms and normal rest ABI [12].…”
Section: Introductionmentioning
confidence: 99%